Reflections on a personalized cognitive rehabilitation intervention: Experiences of people living with dementia and their carers participating in the GREAT trial. Issue 2 (7th February 2022) - Warmoth, Krystal; Morgan-Trimmer, Sarah; Kudlicka, Aleksandra; Toms, Gill; James, Ian A.; Woods, Bob; ,
ABSTRACT: Cognitive rehabilitation for people living with early-stage dementia improves functional ability in areas targeted in the therapy, but little is known about how participants experience this intervention. This qualitative paper investigates participants' views about a cognitive rehabilitation intervention in a randomized controlled trial (the GREAT trial) and aims to help explain and interpret the findings and to inform further intervention development. Using in-depth thematic analysis, 43 semi-structured interviews (35 individual and 8 dyadic) were conducted with 25 people living with dementia and 26 family carers from three sites. The person-centred, individualized approach was valued. Some participants' views about dementia were questioned as a consequence of taking part in the therapy; they considered the effectiveness of the intervention in the context of the progressive nature of the condition. Certain participants continued to be doubtful, focussing on the inevitability of decline, rather than the possibility of reablement. Such views may have influenced engagement. The therapeutic relationship played a vital role as it was how personalized care was provided and participants' views had changed positively. Therapists engendered greater confidence and reduced anxiety and social isolation. Positive responses support personalized rehabilitative care to address the specific needs of people living with dementia.